2012
DOI: 10.1021/ie203022g
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosion Potential of 4-Amino-3-methyl-1,2,4-triazole-5-thione Derivatives (SAMTT and DBAMTT) on Mild Steel in Hydrochloric Acid Solution

Abstract: The corrosion inhibition efficiency of two Schiff bases 4-salicylideneamino-3-methyl-1,2,4-triazole-5-thione (SAMTT) and 4-(2,4-dihydroxybenzylideneamino)-3-methyl-1H-1,2,4-triazole-5(4H)-thione (DBAMTT) on mild steel in hydrochloric acid was tested by weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy. The results revealed that both SAMTT and DBAMTT act as excellent inhibitors, and the inhibition efficiencies obtained from the weight loss and electrochemical experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…A large number of these derivatives exhibit diverse biological properties including anticonvulsant, antidepressant, anti‐inflammatory, antibacterial, antifungal and anticancer activity . In the context of potential industrial applications, several 1,2,4‐triazole‐3‐thiones have shown corrosion inhibition of copper and mild steel in chloride media and acidic solutions …”
Section: Introductionmentioning
confidence: 99%
“…A large number of these derivatives exhibit diverse biological properties including anticonvulsant, antidepressant, anti‐inflammatory, antibacterial, antifungal and anticancer activity . In the context of potential industrial applications, several 1,2,4‐triazole‐3‐thiones have shown corrosion inhibition of copper and mild steel in chloride media and acidic solutions …”
Section: Introductionmentioning
confidence: 99%
“…This is because apart from searching for inhibitors with high efficiency, other factors related to safety and environmental profiles of such chemicals have recently come under severe scrutiny. [11] Benzimidazole is a heterocyclic aromatic compound with a bicyclic structure consisting of the fusion of benzene and imidazole rings, and hydrogen atoms on the rings can be substituted by other groups or atoms. Recently, benzimidazole and its derivatives have received considerable attention because of their good environmental profile and excellent corrosion inhibition performance.…”
Section: Introductionmentioning
confidence: 99%
“…ΔG̊ ads values were evaluated using the values of K ads ,. Studies has shown that the ΔG̊ ads values around −20.0 kJmol −1 indicate the electrostatic interaction between the charged species (MS and NSAIDs) i. e., physisorption , while value around −40.0 kJmol −1 or higher encompass charge sharing or transfer between MS and the inhibitor, i. e., chemisorption ,. As in our case the value of ΔG̊ ads lies between −17.0 to −20.0 kJ mol −1 which indicates the adsorption process to be spontaneous, leading to the formation of more stable inhibitor film on MS surface, thereby demonstrating the adsorption to be a straightforward physisorption phenomenon.…”
Section: Resultsmentioning
confidence: 55%